Modeling of Plasmonic light-trapping design in ultrathin GaSb thermophotovoltaic cell - Zaazaa Khaoula; Boumegouas, Khadhra; Bendelala, Fathi (Université Amar Thelidji- Laghouat FACULTE: DE TECHNOLOGIE DEPARTEMENT D’ELECTRONIQUE, 2023)
This manuscript studies the potential of using a light-trapping strategy based on a Metamaterial structure, which is made for enhancing photon absorption in ultrathin gallium antimonide (GaSb) Thermophotovoltaic (TPV) cells. Through the use of the rigorous Finite Element Method (FEM), and Finite Difference Time Domain (FDTD) approaches using the powerful software CST, it was found that this nanostructured configuration can excite: magnetic polariton (MP), surface plasmon polariton (SPP), and Fabry-Perot (FP) resonances, leading to increased absorption in the active layer. Further discussion was conducted on the influence of geometric parameters, polarization sensitivity, and incidence angle in the absorption peak yielded. Finally, the electrical proprieties with the conversion efficiency of the ultrathin TPV cell-coupled Metamaterial structure have been computed. The maximum cell efficiency that can be obtained is 11.3% under blackbody radiation of 2000k, which is induced by the MP, SPP, and FP phenomena, and directly contribute to enhancing cell conversion efficiency.
FILIERE : Electronique